2009
DOI: 10.1016/s0929-6646(09)60056-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silent Infarction on the Outcome of Stroke Patients

Abstract: The study showed a higher frequency of small artery disease in patients with SIs. First-ever stroke patients with SIs should be considered at high risk for recurrent stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The strength of the present study is that we included patients that underwent multi-modal MRI including DWI, which enables acute ischemic lesion and clinically silent lesions to be more accurately differentiated than conventional MRI. We found that the prevalence of SBI in ischemic stroke patients was within the range delineated by previous MRI studies (20-57%) [16][17][18]. Based on the results of previous studies and the present study, it is evident that the prevalence of SBI is substantially greater in patients with ischemic stroke than in healthy subjects, which suggests that the presence of SBI may reflect an ongoing cerebral vasculopathy and serve as marker of future stroke.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The strength of the present study is that we included patients that underwent multi-modal MRI including DWI, which enables acute ischemic lesion and clinically silent lesions to be more accurately differentiated than conventional MRI. We found that the prevalence of SBI in ischemic stroke patients was within the range delineated by previous MRI studies (20-57%) [16][17][18]. Based on the results of previous studies and the present study, it is evident that the prevalence of SBI is substantially greater in patients with ischemic stroke than in healthy subjects, which suggests that the presence of SBI may reflect an ongoing cerebral vasculopathy and serve as marker of future stroke.…”
Section: Discussionsupporting
confidence: 84%
“…These findings suggest that hypertension is a strong determinant for SBI in both healthy subjects and ischemic stroke patients. Although the clinical consequences of SBI in terms of functional outcomes and stroke recurrence in ischemic stroke have yet to be determined, stroke recurrence may be prevalent in patients with SBI [16], and pre-existing SBI may be a potent predictor of a poor outcome in symptomatic lacunar stroke [36]. Accordingly, strict blood pressure control in the pre-morbid status is required for prevention of future stroke in the presence of silent brain lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for SBI are considered to be comparable to those for stroke; therefore, cardiovascular patients may also be at high risk of silent infarcts with similar risk factors such as ageing, carotid artery stenosis, hypertension, diabetes mellitus and retinal artery stenosis. Age and hypertension are independently and strongly associated with SBI 2,9,10 and Vermeer et al 2 identified absolute risk of stroke within four years at 11.7% for participants with SBI compared with 2.3% for those without SBI.…”
Section: Discussionmentioning
confidence: 99%
“…SBI is thought to be associated with a higher mortality, although results have varied, 10 with the Rotterdam Scan Study 11 finding a prevalence of 20% of SBI in a normal, healthy population aged between 60 and 90 years. The prevalence was strongly affected by age 9 and increased from 8% in the participants aged 60–64 years to 35% in the oldest group (85–90 years).…”
Section: Discussionmentioning
confidence: 99%